2009
DOI: 10.1097/crd.0b013e3181c07592
|View full text |Cite
|
Sign up to set email alerts
|

Short QT Syndrome

Abstract: The past 2 decades have witnessed the emergence of many disease states related to ion-channel disorders, the so-called "channelopathies," usually associated with structurally normal hearts. The initial emphasis was directed toward the congenital long QT syndrome and the Brugada syndrome. Recently, the hereditary short QT syndrome has emerged as yet another rare channelopathy. This autosomal dominant syndrome can afflict infants, children, or young adults; often a remarkable family background of sudden cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
1
23
0
2
Order By: Relevance
“…However, the cause of short QT syndrome is unclear and it has been hypothesized that the QT shortens when heart rate increases (Maltret et al 2014). It has been also proposed that short QT-interval may be acquired (Gaita et al 2004), because some drugs or conditions such as hyperkalemia, acidosis, and hyperthermia could cause induction of short QT-interval in even normal subjects (Patel and Pavri 2009). These hypothesis and data are in line with our present findings.…”
Section: R a F Tsupporting
confidence: 91%
“…However, the cause of short QT syndrome is unclear and it has been hypothesized that the QT shortens when heart rate increases (Maltret et al 2014). It has been also proposed that short QT-interval may be acquired (Gaita et al 2004), because some drugs or conditions such as hyperkalemia, acidosis, and hyperthermia could cause induction of short QT-interval in even normal subjects (Patel and Pavri 2009). These hypothesis and data are in line with our present findings.…”
Section: R a F Tsupporting
confidence: 91%
“…Recent reports suggest that channelopathies play a part to play in the development of atrial fibrillation Johnson et al, 2008;Kaufman, 2009;Patel & Pavri, 2009;Thejus & Francis, 2009). Atrial fibrillation may be associated with genes resulting in either ion channel gain-of-function or loss-of-function Johnson et al, 2008;Kaufman, 2009;Patel & Pavri, 2009;Thejus & Francis, 2009) and may be seen in 2% of patients with long QT syndrome, 10% of patients with Brugada syndrome and 30% of patients with short QT syndrome (Johnson et al, 2008;Patel & Pavri, 2009;Roberts & Gollob, 2010, Thejus & Francis, 2009.…”
Section: Atrial Geneticsmentioning
confidence: 99%
“…Atrial fibrillation may be associated with genes resulting in either ion channel gain-of-function or loss-of-function Johnson et al, 2008;Kaufman, 2009;Patel & Pavri, 2009;Thejus & Francis, 2009) and may be seen in 2% of patients with long QT syndrome, 10% of patients with Brugada syndrome and 30% of patients with short QT syndrome (Johnson et al, 2008;Patel & Pavri, 2009;Roberts & Gollob, 2010, Thejus & Francis, 2009. Familial atrial fibrillation has also been associated with identified channelopathies (Benito et al, 2008;Darbar et al, 2008;Johnson et al, 2008;Kaufman 2009;Patel & Pavri, 2009;Roberts & Gollub, 2010;Thejus & Francis, 2009). Mutations involving ion transport associated with atrial fibrillation include SCN5A, KCNH2, KCNQ1, KCNJ2, KCNE2, KCNA5, HERG + MiRP1, KCNE1 and probably others (Benito et al, 2008;Darbar et al, 2008;Johnson et al, 2008;Kaufman 2009;Patel & Pavri, 2009;Thejus & Francis, 2009).…”
Section: Atrial Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…This enables cells to overcome the electrical suppression generated by Kir channels around the K 1 reversal potential and transiently depolarize the membrane. Appropriate voltage-dependent inhibition of Kir channel activity is essential for normal function of excitable cells, as illustrated by the effects of gain-of-function (loss of polyamine sensitivity) mutations of Kir2.1 that underlie shortening of the QT interval and have been categorized as SQT3 (Priori et al, 2005;Patel and Pavri, 2009). In contrast, ligand-dependent gating involves conformational changes of the channel protein and alters cellular excitability over longer time scales in response to signaling cascades or changes in cellular metabolism (Wickman et al, 1998;Koster et al, 2000).…”
Section: Introductionmentioning
confidence: 99%